The distribution and lifetime of powerful radio galaxies as a function of environment and redshift - David Garofalo (Nature Portfolio, 2018)
Abstract Correlations between jet power and active time for z < 0.1 high excitation and low excitation radio galaxies are explored as well as evidence in favor of a specific, non-random distribution for these objects including mid-infrared emitting radio galaxies as a function of environment and redshift. In addition, so-called weak line radio galaxies with FRII jet morphology have been identified as a class of active galaxies in the process of shutting down. This paper identifies common features between these seemingly disparate phenomena described above for the population of radio galaxies, and strings them together by way of a simple phenomenological framework that has shed light on the radio loud/radio quiet dichotomy, the jet-disk connection, and the distribution of all active galaxies as a function of redshift.